Initial management of omphalocele using negative pressure wound therapy (NPWT) in Ecuador: A case series - Acosta-Farina, Daniel; Aguayo-Vistin, Johan; Cedeño-Moreira, Cristhian; Salinas-Salinas, Vicente; Polit-Guerrero, Verónica; Oliveros-Rivero, Jorge; Acosta-Bowen, Daniel (Journal of Neonatal Surgery, 2022)
Background: Omphalocele is an abdominal wall defect. Herniated organs can be small or large intestine, liver, and stomach. The use of conventional techniques has always been a challenge for the surgeon. The goal of using NPWT is to provide a quick, simple, and effective method to reduce the eviscerated content and enlarge the visceral continent. Case Presentation: The record of 3 patients with omphalocele was reviewed. There were two females and one male neonate. All the babies were born by C-section and were antenatally diagnosed for omphalocele. In all cases, NPWT was applied. Two cases were discharged in good condition while one patient with complex cardiac defects succumbed. Conclusion: NPWT is an effective and safe alternative for omphalocele management.